2016
DOI: 10.2139/ssrn.2766236
|View full text |Cite
|
Sign up to set email alerts
|

When Not in the Best of Worlds: Uncertainty and Forest Carbon Sequestration

Abstract: It is argued that the forest can provide low-cost options to reduce the atmospheric CO2 concentration. However, many dimensions of the future dynamics of the forest, and its interactions with climate change are still not well understood. This paper provides new insights into how these types of uncertainties affect the optimal climate policy. We model uncertainty over several key forest parameters by using the novel state-contingent approach.Our main results show that the importance of including optimal forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…On the other hand, it would be difficult to estimate such functions at regional and national scale while including our explanatory variables of interest. Nevertheless, our estimates of intrinsic forest growth rate for Sweden are close to results obtained in other studies (Eriksson and Vesterberg 2016). We cannot compare our results on the effect of site quality on forest growth and value of timber and carbon sequestration, since we are not aware of any similar studies.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…On the other hand, it would be difficult to estimate such functions at regional and national scale while including our explanatory variables of interest. Nevertheless, our estimates of intrinsic forest growth rate for Sweden are close to results obtained in other studies (Eriksson and Vesterberg 2016). We cannot compare our results on the effect of site quality on forest growth and value of timber and carbon sequestration, since we are not aware of any similar studies.…”
Section: Discussionsupporting
confidence: 73%
“…The significant estimate of 0.13 is close to the estimates of intrinsic growth rate in boreal forests at the large scale, which amounts to 0.11 (e.g. Eriksson and Vesterberg 2016). Standing volume has the expected negative sign, i.e.…”
Section: Site Quality and Forest Productivitysupporting
confidence: 71%
See 1 more Smart Citation
“…Some previous studies have suggested that the global temperature will reach the 2 • C increase between 2026 and 2060 [22]. Increasing temperatures affect forests by changing their geographical distributions [23] and exhibit dominant control over the natural distribution of forest ecosystems [24]. Temperature increases will change the regeneration capacities [25] of species and therefore alter the area of suitable habitat of forest vegetation.…”
Section: Introductionmentioning
confidence: 99%